Mesophilic and thermophilic photo-hydrogen production from micro-grinded, enzyme-hydrolyzed maize straws. (9th November 2017) - Hu, Jianjun; Jing, Yanyan; Zhang, Quanguo; Guo, Jie; Lee, Duu-Jong
Abstract: Photo-fermentative is an endothermic reaction driven by light energy to overcome the energy barrier. This communication conducted photo-fermentation hydrogen tests with micro-grinded, enzyme-hydrolyzed maize straws considering the effects of broth temperature ranging 28.2–54.5 °C. The hydrogen production rate was first increased with broth temperature, peaked at 39.6 °C, and then decreased at higher temperature range. The photo-fermentative process can be approximated as a catalytic reaction with positive activation energy and positive activation entropy, an endothermic, entropy-driven complexation process. Highlights: Photofermentative hydrogen production was tested at meso to thermophilic conditions. Positive activation energy was noted at mesophilic condition. Negative temperature dependence was noted at thermophilic condition. Activation energy was estimated based on data from mesophilic tests.